Digital Da'wah Trends in the Age of Social Media: A Bibliometric Analysis - Rully Khairul Anwar; Fitriani Faudzini; Mualimin Mualimin (Ilmu Dakwah: Academic Journal for Homiletic Studies, 2025)
This study aims to answer five main research questions regarding the trends of digital da'wah in the age of social media: 1) How have scientific publications on digital da'wah evolved in recent years? 2) Who are the most productive researchers and institutions in this field? 3) What keywords and topics appear frequently in the literature on digital da'wah? 4) How have research issues on digital da'wah developed over time? 5) What academic databases are the main sources of publications on digital da'wah? The research method used is bibliometric analysis of 274 scholarly articles published between 2009 and 2024. Data were gathered from the Dimensions database using relevant keywords related to digital da'wah. The results show a significant growth in scholarly publications on digital da'wah, with an increasing number of articles published each year. The study also identifies the most productive researchers and institutions, as well as the most frequently used keywords in the literature. Furthermore, this research highlights major challenges in digital da'wah, such as misinformation, religious polarization, and ethical issues. The impact of this study provides a systematic overview of digital da'wah trends and helps researchers and practitioners understand the dynamics of da'wah in the digital era.